Is nationwide special campaign on antibiotic stewardship program effective on ameliorating irrational antibiotic use in China? Study on the antibiotic use of specialized hospitals in China in 2011–2012 - Zou, Xiao-xu; Fang, Zi; Min, Rui; Bai, Xue; Zhang, Yang; Xu, Dong; Fang, Peng-qian (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
Summary With dwindling number of new antibiotics and inappropriate use of antibiotics, the emergence and spread of antibiotics resistance occurs commonly in healthcare institutions worldwide. In China, antibiotics are commonly overprescribed and misused. This study is to assess the effect of the nationwide special campaign on antibiotic stewardship program (ASP) at specialized hospitals in China by investigating prescription information from 2011 to 2012. Data on the hospital consumption and prescription of systemic antibiotics were obtained from four specialized hospitals, including maternity, children’s, stomatological and cancer hospitals. Systematic random sampling was used to select outpatient prescriptions and inpatient cases. A total of 105 specialized hospitals in 2011 and 121 specialized hospitals in 2012 were analysed. The defined daily doses (DDDs) per 100 inpatient days, the percentage of antibiotic use in outpatient prescriptions, and the percentage of antibiotic use in inpatient cases were used as measurements of antibiotic use. The overall antibiotic use density in the selected hospitals decreased between 2011 and 2012 from 39.37 to 26.54 DDD/100 inpatient days ( P <0.001). The percentage of antibiotic use in outpatient prescriptions (range: 24.12%–18.71%, P =0.109) and inpatient cases (64.85%–60.10%, P =0.006) also decreased within the two years. Significant changes were observed among regions and different hospitals within the two years. And antibiotic consumption was correlated with the type and size of specialized hospital in 2012, but not with the regions. This analysis of antibiotic consumption of specialized hospitals allows relevant comparisons for benchmarking and shows that national ASP has improved antibiotic rational use in China. The data will assist policymakers in formulating effective strategies to decrease antibiotic overuse and identify areas that require further work.